Study on Cissus quadrangularis Linn: An Insilico Approach towards the Anti-inflammation and Anticancer - Vidya Edathil; Selvi Gopal (New Innovations in Chemistry and Biochemistry Vol. 3, 2021)
Cissus quadrangularis, is a medicinal plant indigenous to Asia and Africa. It is used in indigenious system of medicine like ayurveda, siddha, unani and homoeopathy. The active compounds isolated from this plant are considered to be very effective for various ailments. Ethanobotanical and traditional uses of the plant Cissus quadrangularis has initiated the phytochemical investigation of the plant. The main objective of the study is to identify the potential of few isolated phytochemicals from this plant against cancer and inflammation by insilico method. The stem of the plant was subjected for successive solvent extraction with Petroleum ether, Ethyl acetate, Chloroform and Ethanol. The crude extract was column choromatographed. Among the 20 constituents isolated ascorbic acid, quercetin, phytol, and Luteolin were identified. Later, those phytochemicals were subjected for molecular docking in Auto dock 4.2 to examine their pharmacological activity. The results obtained showed that these compounds can be further carry over for invivo analysis.